Continuous casting covering slag based on addition of biomass ash and preparation method of continuous casting covering slag
By adding alkali metal components in biomass ash to the continuous casting protective slag, the problem of insufficient performance and stability of traditional protective slag under high temperature conditions is solved, and the low melting point, good fluidity and high chemical stability of the protective slag are achieved, thereby improving the surface quality of the casting billet and the stability of the continuous casting process.
Patent Information
- Application Number
- CN202510193092.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-04-15
AI Technical Summary
The performance and stability of traditional continuous casting protective slag under high temperature conditions are limited, and the surface quality of the casting billet and the smooth continuous casting process are not sufficiently guaranteed.
By adding the alkali metal components in the biomass ash to the protective slag, replacing the original alkali metal oxides, adjusting the chemical composition and physical properties of the protective slag, and improving its fluidity, lubricity and chemical stability.
It achieves low melting point, good fluidity and high chemical stability of the protective slag, improves the surface quality of the casting billet and the stability of the continuous casting process, and is in line with the development trend of green metallurgy and circular economy.
Smart Images

Figure CN119819892A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of continuous casting protection slag materials and relates to a continuous casting protection slag based on adding biomass ash and a preparation method thereof. Background Art
[0002] The existing continuous casting protection slag is mainly based on CaO-SiO2-A12O3, and fluxes such as CaF2, Li2O, and Na2O need to be added. It is mainly used in the continuous casting process to play many important functions such as heat insulation, preventing secondary oxidation of molten steel, absorbing non-metallic inclusions, lubricating the billet shell, and controlling heat transfer. Among them, lubrication and heat transfer functions are the most important. It plays an extremely important role in improving the surface quality of the billet and ensuring the smooth progress of the continuous casting process. The development history of continuous casting protection slag can be summarized into the following stages: the 1960s was the stage of trial production and development and initial application of continuous casting protection slag, the 1970s was the frequent stage of research, development and application of continuous casting protection slag, the 1980s was the further development stage of research and application of continuous casting protection slag, and the 1990s was the mature stage of continuous casting protection slag development. With the emergence of computer-aided design technology, protective slag suitable for casting various types of steel has been developed, and the varieties have been further enriched. At present, according to the needs of special components of high value-added steel grades, continuous casting protective slag has carried out deeper research in the direction of more reasonable matching with steel grades and further improving the quality of castings.
[0003] Traditional mold slags are mainly composed of oxides and salts, but their performance and stability under high temperature conditions have certain limitations. In recent years, with the improvement of environmental awareness and the demand for resource recycling, biomass ash, as a renewable resource, has received widespread attention because it is rich in alkali metal elements (such as sodium, potassium, etc.). Alkali metals in biomass ash can effectively reduce the melting point of mold slag, improve its fluidity and covering ability, and enhance the chemical stability of the slag. Alkali metal ions can destroy the original dense network structure of silicates, effectively reduce the melting point, optimize the melting rate, ensure that the mold slag is accurately and timely melted in the key temperature range of continuous casting, and form a stable and adaptive slag film. In terms of lubrication, alkali metals can adjust the viscosity to the ideal range, reduce the friction between the ingot and the crystallizer wall, and synergistically improve the uniformity of heat transfer. In addition, alkali metal elements can react with other components in the slag to generate low-melting point compounds, further optimize the smelting process, and reduce the wear and heat loss of the smelting furnace body at high temperatures. Therefore, applying the alkali metal components in biomass ash to the formulation of protective slag can not only improve the smelting efficiency, but also realize the resource utilization of biomass ash, which is in line with the development trend of green metallurgy and circular economy.
[0004] In the prior art, patent publication number CN117340211A discloses a low-melting-point composite molten salt protective slag and its preparation process. The protective slag uses an inorganic non-metallic molten salt system as a basic material, so that the protective slag has good fluidity and lubricity. At the same time, alkali metal oxides are added. The added alkali metal oxides and carbonates are decomposed under high temperature conditions. The metal ions can form a bond with one corner of the silicon-oxygen tetrahedron in the silicate, preventing the silicon-oxygen tetrahedron from forming a network chain or disconnecting the network chain, thereby improving the fluidity of the protective slag and improving the wettability. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a continuous casting protection slag based on the addition of biomass ash and a preparation method. The protection slag selects to add biomass ash rich in alkali metals to the components to replace its original alkali metals, so that the protection slag has good physical and chemical properties.
[0006] To achieve the above object, the present invention is implemented through the following technical solutions:
[0007] A continuous casting mold slag based on adding biomass ash, the chemical composition and mass percentage of the mold slag are:
[0008] CaO: 45% ~ 50%, SiO2: 35% ~ 45%, Al2O3: 1.5% ~ 2.5%, K2O: 2% ~ 10%, B2O3: 5% ~ 7%, and the balance is unavoidable impurities.
[0009] The mass ratio of CaO to SiO2 in the chemical composition of the protective slag satisfies: CaO / SiO2=1.15.
[0010] The sources of K2O, part of CaO and part of SiO2 in the chemical composition of the protective slag are biomass ash.
[0011] The biomass ash is straw ash.
[0012] The basicity of the protective slag is 1.1-1.3.
[0013] The physical properties of the protective slag meet the following requirements: melting point 1080-1150° C.; viscosity 0.1-0.2 Pa·S at 1300° C.
[0014] The melting speed of the protective slag is 15 to 35 seconds.
[0015] The average heat flux density of the protective slag is 0.90-1.20 MW / m 2 .
[0016] A method for preparing continuous casting mold slag based on adding biomass ash comprises the following steps:
[0017] 1) The amount of raw materials is calculated and weighed according to the target composition, and the raw materials are mixed evenly using a mixer;
[0018] 2) using a rotary kiln to heat the mixed raw materials at 1300-1500°C until they are melted;
[0019] 3) The heated molten liquid protective slag is quickly cooled by water cooling process;
[0020] 4) The cooled slag block is initially crushed by a jaw crusher and then finely ground by a ball mill to obtain protective slag powder of the required particle size.
[0021] The protective slag powder obtained in step 4) is below 200 mesh.
[0022] The role and proportion of each main raw material in the present invention are determined as follows:
[0023] (1) CaO: Calcium oxide can adjust the basicity of the mold slag, effectively absorb inclusions in the molten steel, improve the lubrication performance of the slag on the ingot, maintain the stability of the slag layer structure, and prevent the secondary oxidation of the molten steel during the casting process, thereby improving the quality of the ingot, which is of great significance to the smooth progress of the continuous casting process. The basicity of the mold slag is designed to be 1.0-1.3, and at the same time, the mold slag is guaranteed to have good crystallization performance, so the CaO content is controlled at 45%-50%.
[0024] (2) SiO2: Silica is an important component in the mold slag. Its main function is to adjust the viscosity and melting temperature of the mold slag, and to coordinate with calcium oxide and other components to control the basicity, which affects the crystallization performance of the slag. It participates in the formation of the glass phase to ensure that the mold slag is balanced between the crystalline and amorphous states, thereby optimizing the lubrication, heat transfer and inclusion absorption functions of the mold slag. In the present invention, the basicity of the slag is designed to be 1.0-1.3, and the SiO2 content is controlled to be 35%-45%, preferably 40%-45%.
[0025] (3) Al2O3: The role of aluminum oxide in mold slag is mainly reflected in improving the melting point and stability of the slag. It has strong anti-reduction properties, can inhibit the reduction of components in the slag, and improve the slag's anti-corrosion ability. At the same time, it can also improve the fluidity of the slag, optimize the deoxidation and desulfurization process of the molten steel, and ensure the quality of the molten steel. In the present invention, in order to ensure that the mold slag has strong stability and fluidity, the Al2O3 content is controlled to be 1.5% to 2.5%.
[0026] (4) K2O: Potassium oxide is a key flux component in the mold slag. It can significantly reduce the melting point and viscosity of the mold slag, promote the rapid melting of the mold slag to form a uniform slag liquid, improve the fluidity of the slag, facilitate uniform spreading on the surface of the ingot, enhance the lubrication effect on the ingot, and help regulate the heat transfer rate of the mold slag to ensure stable and efficient continuous casting. In the present invention, in order to ensure that the mold slag has a certain lubricity, the K2O content is controlled to be 2% to 10%, preferably 6% to 8%.
[0027] (5) B2O3: Boron trioxide plays multiple roles in mold slag, such as lowering melting point, improving fluidity, enhancing chemical stability, promoting deoxidation and desulfurization, and improving mechanical properties, thereby improving the comprehensive performance of the mold slag and the smelting quality of molten steel. In the present invention, in order to ensure that the mold slag has a lower viscosity and overall structural strength, the B2O3 content is controlled to be 5% to 7%, preferably 6%.
[0028] (6) Biomass ash: Biomass ash contains calcium, magnesium, potassium, sodium and other components, which can effectively reduce the melting point of protective slag, improve the fluidity and coverage of slag, thereby protecting the surface of liquid metal and reducing oxidation reaction; the minerals in biomass ash can improve the stability of slag, prevent slag layer ablation or uneven flow, and ensure the stability of slag layer during continuous casting. In addition, biomass ash can also react with harmful elements (such as sulfur and phosphorus) in molten steel to play a role in desulfurization and dephosphorization, thereby improving the purity and quality of molten steel.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The protective slag of the present invention adds part of biomass straw ash to partially replace the alkali metal oxides in the protective slag. The alkali metal oxides in the biomass ash decompose under high temperature conditions, and the metal ions can form coordination with the silicon oxygen tetrahedron in the silicate, destroying its network structure, thereby improving the fluidity of the protective slag and improving the wettability. In addition, the biomass ash can also generate a new crystalline mineral phase of calcium borosilicate (Ca 11 Si4B2O 22 ), the grain size of the generated calcium borosilicate crystals is 1 to 5 μm, replacing the gunite in the traditional fluorine-containing protective slag. This not only reduces the melting point, improves fluidity, and enhances chemical stability, but also promotes deoxidation and desulfurization reactions and improves its mechanical properties, thereby improving the comprehensive performance of the protective slag and the smelting quality of the molten steel. The protective slag has good fluidity and lubricity.
[0031] The protective slag of the present invention controls the appropriate CaO / SiO2 ratio and the amount of K2O added. CaO and SiO2 are the main components of the protective slag, and controlling the appropriate CaO / SiO2 ratio determines the physical and chemical properties of the protective slag to the greatest extent; then by controlling the appropriate amount of K2O added, the melting point and viscosity of the protective slag can be significantly reduced, the original Si-O-Si bond and BOB bond are destroyed, the protective slag structure becomes simple, and the formation of calcium borosilicate is greatly promoted.
[0032] During use, the mold slag can generate evenly distributed calcium borosilicate (Ca 11 Si4B2O 22 ) crystals. The grain size of the generated calcium borosilicate crystals is 1 to 5 μm. The appropriate amount of crystal precipitation and its appropriate size distribution significantly optimize the heat transfer process, thus creating the necessary conditions for the production of high-quality steel. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0034] The present invention is described in detail below in conjunction with the accompanying drawings, but it should be noted that the implementation of the present invention is not limited to the following embodiments. The content of components in the steel and the content of components in the slag described in the present invention are all mass percentages.
[0035] Example 1
[0036] The chemical composition and mass percentage of the continuous casting mold slag based on the addition of biomass ash are:
[0037] The binary basicity CaO / SiO2 is 1.15; CaO: 48.25%, SiO2: 41.95%, Al2O3: 1.8%, K2O: 2%, B2O3: 6%, and the remainder are unavoidable impurities.
[0038] Preparation process of continuous casting mold slag based on adding biomass ash: Figure 1 As shown, the amount of raw materials is weighed according to the above target composition, and the raw materials are evenly mixed using a mixer to ensure that each component is evenly dispersed; then a rotary kiln is used to heat and melt the mixed sample at 1300-1500°C, and liquid protective slag is formed through continuous high-temperature melting to ensure that the components are fully reacted and homogenized to form a uniform slag. The molten liquid protective slag is quickly cooled by a water cooling process to form a protective slag block with a good glassy structure. The cooled slag block is initially crushed by a jaw crusher, then finely ground by a ball mill, and then graded and screened to obtain a finished protective slag with a particle size that meets the requirements of the steel continuous casting process.
[0039] The main physical properties of mold slag are shown in Table 1.
[0040] Example 2
[0041] The chemical composition and mass percentage of the continuous casting mold slag based on the addition of biomass ash are:
[0042] The binary basicity CaO / SiO2 is 1.15; CaO: 47.18%, SiO2: 41.02%, Al2O3: 1.8%, K2O: 4%, B2O3: 6%, and the remainder are unavoidable impurities.
[0043] Preparation process: Same as Example 1.
[0044] The main physical properties of mold slag are shown in Table 1.
[0045] Example 3
[0046] The chemical composition and mass percentage of the continuous casting mold slag based on the addition of biomass ash are:
[0047] The binary basicity CaO / SiO2 is 1.15; CaO: 46.11%, SiO2: 40.09%, Al2O3: 1.8%, K2O: 6%, B2O3: 6%, and the remainder are unavoidable impurities.
[0048] Preparation process: Same as Example 1.
[0049] The main physical properties of mold slag are shown in Table 1.
[0050] Example 4
[0051] The chemical composition and mass percentage of the continuous casting mold slag based on the addition of biomass ash are:
[0052] The binary basicity CaO / SiO2 is 1.15; CaO: 45.04%, SiO2: 39.16%, Al2O3: 1.8%, K2O: 8%, B2O3: 6%, and the remainder are unavoidable impurities.
[0053] Preparation process: Same as Example 1.
[0054] The main physical properties of mold slag are shown in Table 1.
[0055] Preparation process: Same as Example 1.
[0056] The main physical properties of mold slag are shown in Table 1.
[0057] Table 1 Main physical properties of mold slag
[0058]
[0059] The protective slag of the present invention adds part of biomass straw ash to partially replace the alkali metal oxides in the protective slag. The alkali metal oxides in the biomass ash decompose under high temperature conditions, and the metal ions can form coordination with the silicon oxygen tetrahedron in the silicate, destroying its network structure, thereby improving the fluidity of the protective slag and improving the wettability. In addition, the biomass ash can also generate a new crystalline mineral phase of calcium borosilicate (Ca 11 Si4B2O 22 ), replacing the gunite in the traditional fluorine-containing protective slag. This not only reduces the melting point, improves fluidity, and enhances chemical stability, but also promotes deoxidation and desulfurization reactions and improves its mechanical properties, thereby improving the comprehensive performance of the protective slag and the smelting quality of the molten steel.
Claims
1. A continuous casting mold slag based on adding biomass ash, characterized in that: The chemical composition and mass percentage of the mold slag are: CaO: 45% ~ 50%, SiO2: 35% ~ 45%, Al2O3: 1.5% ~ 2.5%, K2O: 2% ~ 10%, B2O3: 5% ~ 7%, and the balance is unavoidable impurities.
2. The continuous casting mold slag based on adding biomass ash according to claim 1, characterized in that: The mass ratio of CaO to SiO2 in the chemical composition of the protective slag satisfies: CaO / SiO2=1.
15.
3. The continuous casting mold slag based on adding biomass ash according to claim 1, characterized in that: The sources of K2O, part of CaO and part of SiO2 in the chemical composition of the protective slag are biomass ash.
4. The continuous casting mold slag based on adding biomass ash according to claim 3, characterized in that: The biomass ash is straw ash.
5. The continuous casting mold slag based on adding biomass ash according to claim 1, characterized in that: The basicity of the protective slag is 1.1-1.
3.
6. The continuous casting mold slag based on adding biomass ash according to claim 1, characterized in that: The physical properties of the protective slag meet the following requirements: melting point 1080-1150° C.; viscosity 0.1-0.2 Pa·S at 1300° C.
7. The continuous casting mold slag based on adding biomass ash according to claim 1, characterized in that: The melting speed of the protective slag is 15 to 35 seconds.
8. The continuous casting mold slag based on adding biomass ash according to claim 1, characterized in that: The average heat flux density of the protective slag is 0.90-1.20 MW / m 2 .
9. A method for preparing continuous casting mold slag based on adding biomass ash according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1) The amount of raw materials is calculated and weighed according to the target composition, and the raw materials are mixed evenly using a mixer; 2) using a rotary kiln to heat the mixed raw materials at 1300-1500°C until they are melted; 3) The heated molten liquid protective slag is quickly cooled by water cooling process; 4) The cooled slag block is initially crushed by a jaw crusher and then finely ground by a ball mill to obtain protective slag powder of the required particle size.
10. The method for preparing continuous casting mold slag based on adding biomass ash according to claim 9, characterized in that: The protective slag powder obtained in step 4) is below 200 mesh.
Citation Information
Patent Citations
Low-melting-point composite molten salt casting powder and preparation process thereof
CN117340211A